Lupus Pancreatitis: A Rarely Revealing Condition of Systemic Lupus Erythematosus about a Case - El Azzam, Naima; Nkhaili, Asmaa; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
Pancreatitis as an initial manifestation of systemic lupus erythematosus is rare. one case is reported of young female patients who presented with fever, abdominal pain, vomiting and elevated levels of pancreatic enzymes. They were diagnosed with acute severe pancreatitis associated with systemic lupus erythematosus. There are a few reports in the literature about this association, but the pathogenesis and treatment are still controversial.